Anatomical mapping of whole-brain monosynaptic inputs to the orbitofrontal cortex - Yang, Mei; Yang, Hailing; Shen, Lang; Xu, Tonghui (Frontiers in Neural Circuits, 2025)
The orbitofrontal cortex (ORB) exhibits a complex structure and diverse functional roles, including emotion regulation, decision-making, and reward processing. Structurally, it comprises three distinct regions: the medial part (ORBm), the ventrolateral part (ORBvl), and the lateral part (ORBl), each with unique functional attributes, such as ORBm’s involvement in reward processing, ORBvl’s regulation of depression-like behavior, and ORBl’s response to aversive stimuli. Dysregulation of the ORB has been implicated in various psychiatric disorders. However, the neurocircuitry underlying the functions and dysfunctions of the ORB remains poorly understood. This study employed recombinant adeno-associated viruses (rAAV) and rabies viruses with glycoprotein deletion (RV-ΔG) to retrogradely trace monosynaptic inputs to three ORB subregions in male C57BL/6J mice. Inputs were quantified across the whole brain using fluorescence imaging and statistical analysis. Results revealed distinct input patterns for each ORB subregion, with significant contributions from the isocortex and thalamus. The ORBm received prominent inputs from the prelimbic area, agranular insular area, and hippocampal field CA1, while the ORBvl received substantial intra-ORB inputs. The ORBl exhibited strong inputs from the somatomotor and somatosensory areas. Thalamic inputs, particularly from the mediodorsal nucleus and submedial nucleus of the thalamus, were widespread across all ORB subregions. These findings provide novel insights into the functional connectivity of ORB subregions and their roles in neural circuit mechanisms underlying behavior and psychiatric disorders.